When multiple cooperative communication: virtual real-time service theory and application - Wei Chen (Dianxin kexue)
A novel communication service methodology, virtual real-time service, was proposed to discover and utilize the rich temporal and spectrum resource hidden in the negative time axis. Thanks to the delay tolerance of embedded wireless pushing,it could help to unify the content demand of different users,so as to achieve significant spectral and energy efficiency gains of wireless multicasting. The three extensions of cognition object, time scale, and coordination range, induced by virtual real-time service were described. The consumption of computation and storage resource was a cost to be paid for the gains of the energy and spectral efficiency.Hence,the multi-unit collaboration of computation （including cognition）, storage, and communications units was highly desired to minimize the cost of computation and storage resource, while maximize the energy and spectral efficiency gains. The proposed scheme holds the promise of overcoming the stringent restrain on the spectral efficiency,which is caused by the current communication architecture and its underlying theory. The union of its two main characteristics, namely, time non-homogenous transmission and multi-unit collaboration,are expected to form a paradigm-shift theory on time non-homogenous multi-unit collaboration communications.